Tek parti döneminde Giresun valileri (1923-1950) - Kesik, Özgür (Muş Alparslan Üniversitesi, 2025)
Giresun'un 1923-1950 yılları arasında görev yapan mülki idare amirlerini konu alan bu tezde bölgenin idari tarihine yönelik ayrıntılı inceleme sunmak amaçlanmaktadır. Türkiye Cumhuriyeti'nin kurulmasıyla beraber Osmanlı Dönemindeki bürokratik yapı yeni rejime miras olarak kalmıştır. Cumhuriyetle beraber yönetim biçimi ve kurumlar değişse de özünü korumuştur. Vali, vilayetin yöneticisi olarak sürekli önemli bir konumda olmuştur. Devlet başkanının illerdeki temsilcisi olması nedeniyle devlet ve millet arasında köprü vazifesi görmüştür. Tezde Giresun'un il olmasından sonra valilik kurumu ve Giresun'da görev yapan valilerin 1923-1950 yıllarındaki faaliyetleri konu edinilmiştir. 1923-1950 yıllarında Giresun'da görev yapan valilerin biyografilerine yer verilmiş, valilerin imar, eğitim, ekonomi, sanat, ulaşım, tarım, hayvancılık ve sağlık 11 kente olan katkıları ele alınmıştır. Bu tarihlerde görev yapan valilerin, şehrin kalkınması için canla başla çalıştıkları, tüm ülke genelinde olduğu gibi cumhuriyet rejimine yakışır bir Giresun meydana getirmek için yoğun gayret gösterdikleri gözlemlenmiştir. Anahtar Kelimeler: Mülki İdare, Vali, Cumhuriyet Dönemi, Giresun Vilayeti, Modernleşme.

This thesis examines the civil administrative governors who served in Giresun between 1923 and 1950, aiming to present a detailed analysis of the region's administrative history. With the establishment of the Republic of Turkey, the bureaucratic structure of the Ottoman era was inherited by the new regime. Although the form of government and its institutions changed with the Republic, their essence largely remained intact. The governor has consistently held a prominent position as the head of provincial administration. Serving as the representative of the head of state in the provinces, the governor has acted as a bridge between the state and the people. This study focuses on the governorship institution in Giresun following its designation as a province and investigates the activities of the governors who served there between 1923 and 1950. In this regard, the biographies of the governors who served in Giresun between 1923 and 1950 are presented, along with an examination of their contributions to the city in areas such as urban development, education, economy, arts, transportation, agriculture, animal husbandry, and healthcare. It has been observed that the governors of this period worked with great dedication toward the development of the city and made significant efforts to create a Giresun befitting the ideals of the republican regime, as was the case across the country. Key Words: Civil Administration, Governor, Republican Era, Giresun Province, Modernization.
Governors of Giresun during the single-party era (1923–1950)
Keywords: Tarih